على عملية البلعمة خارج الجسم الحي Staphylococcus aureus دراسة تاثير الفا هيمولايسين المنتج من - ابو ريشة, رسمية; سلوم, دنيا; خليل, لميس (Iraqi Journal of Science, 2025)
Hemolysin- of Staphylococcus aureus was purifed by cooling centrifuge at 6.000 r.p.m. for 1/2 hr. And fliterate by using milipore filter (0.22 m).The effect of crude hemolysin on phagocytosis process was studied by measuring the phagocytic index for 20 blood sample which was collected from healthy with control blood samples.From the result we found that the phagoctic index of blood sample which was treated with -hemolysin was 52.2% while the phagocyte index of control blood sample was 76.6%